Pengaruh Human Capital dan Marketing Capability terhadap Kinerja Keuangan dan Nilai Pasar Perusahaan di Sektor Perdagangan Besar Barang Produksi dan Perdagangan Eceran (Kapitalisasi sedang dan Besar) - Ellenora Willi Yuliana; Sarce Elsye Hatane (Business Accounting Review, 2016)
This study aimed to examine the relationship between intellectual capital and marketing capability to financial performance of the company that measured by profitability, and company’s value. The sample of the study was in the trade sector of goods industry and retail trade of medium and big capitalization listed in Indonesia Stock Exchange (IDX). Data were collected from the annual reports for the period of 2009-2014. The total number of observations was 85 firm year. The hypotheses tested by using Multiple Linear Regression. The intellectual capital measured byusingeach component of valueaddedhuman capital. Marketingcapability was measured by using marketing and R&D expenditures, while profitability measured by using Return on Assets. Company’s value measured by using Tobin's q. Variable control used were company size and company age. The results showed that value added human capital had significant influence to profitability and market value of the company, and there was also significant positive influence of company size to market value.